2002
DOI: 10.1200/jco.2002.12.075
|View full text |Cite
|
Sign up to set email alerts
|

Biweekly Chemotherapy With Oxaliplatin, Irinotecan, Infusional Fluorouracil, and Leucovorin: A Pilot Study in Patients With Metastatic Colorectal Cancer

Abstract: This biweekly regimen is feasible and has acceptable and manageable toxicities and no apparent relevant pharmacokinetics interactions. This combination is associated with a promising antitumor activity, time to progression, and survival. A phase III randomized trial in Italy planned by the Gruppo Oncologico Nord Ovest has just started.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
101
3
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(120 citation statements)
references
References 32 publications
5
101
3
4
Order By: Relevance
“…Souglakos et al (2006) reported a 57% response rate when irinotecan and oxaliplatin were given 'up front' with 5-FU to a cohort of 57 patients. Falcone et al (2002) reported a higher response rate (71%) using a similar combination, as well as a 26.5-month overall survival and a 10.4-month PFS, which was comparable with the 8.8 months observed in our study. To our knowledge, there are no published studies combining irinotecan and oxaliplatin concurrently with the other major oral fluoropyrimidine, capecitabine, as a first-line treatment.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Souglakos et al (2006) reported a 57% response rate when irinotecan and oxaliplatin were given 'up front' with 5-FU to a cohort of 57 patients. Falcone et al (2002) reported a higher response rate (71%) using a similar combination, as well as a 26.5-month overall survival and a 10.4-month PFS, which was comparable with the 8.8 months observed in our study. To our knowledge, there are no published studies combining irinotecan and oxaliplatin concurrently with the other major oral fluoropyrimidine, capecitabine, as a first-line treatment.…”
Section: Discussionsupporting
confidence: 90%
“…One way forward, therefore, might be to combine a fluoropyrimidine with both oxaliplatin and irinotecan in the first-line setting so that a patient receives all three drugs 'up front'. Previous studies of irinotecan and oxaliplatin with 5-FU have reported high response rates and impressive survival times (Falcone et al, 2002;Souglakos et al, 2006), suggesting that further investigation of concurrent administration of all three drugs is warranted in the first-line management of patients with metastatic colorectal cancer.…”
mentioning
confidence: 99%
“…Eighty-four out of 124 patients (67.7%) received OHP as a first-line treatment. Fifty-five patients (44.3%) were treated with a FOLFOX-4 regimen De Gramont et al, 2000), 34 patients (27.4%) with FOLFOX-3 regimen , 30 patients (24.1%) with the association of OHP/CPT-11/c.i.5-FU/FA regimen (Falcone et al, 2002), three patients (2.4%) with OHP alone (Diaz-Rubio et al, 1998) and two patients (1.6%) with OHP/ Raltitrexed regimen (Seitz et al, 1999). All patients received a standard antiemetic treatment with ondansetron 8 mg by a i.v.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, a high incidence of severe neutropenia, associated with greater use of haematopoietic growth factors, is often reported when 5-FU, L-HOP, and CPT-11 are simultaneously combined (Falcone et al, 2002;Souglakos et al, 2002). Hand -foot syndrome, which is frequently described with the use of continuous 5-FU infusions or capecitabine (Van Cutsem et al, 2000), was never observed, possibly because the profile of frequent oral UFT/ LV dosing may resemble that of a repeated mini-bolus (Ho et al, 1998) and the UFT dose (250 m À2 day À1 ) was lower than the 300 -350 mg m À2 day À1 used by other authors.…”
Section: Discussionmentioning
confidence: 99%